Factors Affecting Business Rice Farmers Production In Newgae Village Mallawa District , Maro S Regency - Manawiyah Tamamala (Income Journal Of Economics Development, 2021)
This research was conducted in Barugae Village, Mallawa District, Maros Regency. Factors of production is an absolute requirement in a production process. In agriculture, the factors of production consist of land, labor, seeds, fertilizers, pesticides. Each of these production factors has different functions and benefits and influences each other. If one of the production factors is not met, then the production process in agriculture is hampered and cannot run. Barugae Village, Mallawa District, Maros Regency where the residents make a living as rice farmers. This study uses a quantitative descriptive research, the data source comes from as many as 215 people, with a sample of 30 respondents representing all farmers. With data processing techniques using multiple linear regression with the help of SPSS 25 software for windows. The results of this study indicate that the variable land area (X1) has a positive and significant effect on the variable rice production (Y). The labor variable (X2) has a positive and significant effect on the rice production variable (Y). The seed variable (X3) has a positive and significant effect on the rice production variable (Y). The fertilizer variable (X4) has a positive and significant effect on the rice production variable (Y). The pesticide variable (X5) has no positive and insignificant effect on the rice production variable (Y).